Lightweight Rsa Algorithm Using Three Prime Numbers - M. Abd Zaid, Mustafa; Soukaena Hassan, Dr. (International Journal of Engineering and Technology, 2018)
The computing devices utilized as a part of an extensive class of remote correspondence systems, for example, cell phones, remote sensor systems (WSNs), vehicular ad hoc networks (VANETs), mobile ad hoc networks (MANETs), Internet of Things (IoT), body area networks (BANs) and so on, are little and asset compelled. In the current developments of the resource constraint environments, the trend is shifted towards lightweight cryptographic algorithm. Many lightweight cryptographic algorithms have been developed and also existed algorithms are modified in terms of resource constraint environments. One of such new procedures is utilizing three prime numbers for RSA cryptosystem, which is not easily breakable. Our approach using three prime number rather than two prime-dependent systems to get (n) with same length of standard RSA but less bits for prime numbers. The suggested algorithm has speed enhancement on standard RSA key generation side and decryption side by utilizing three primes and the Chinese Reminder Theorem (CRT). The results indicate that the average of speed improvement is ~80% in key generation process, ~96% in decryption process, and only 4% in the encryption process.Â Â Â